2016
DOI: 10.1016/j.ydbio.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a key role for permeability glycoprotein in enhancing the cellular defense mechanisms of fertilized oocytes

Abstract: Double strand breaks (DSBs) are highly damaging DNA lesions that can destabilize the genome and generate a suite of adverse physiological outcomes in the oocyte and early embryo. While it is therefore likely that these cells possess a sophisticated suite of protective mechanisms to ameliorate such damage, the precise nature of these defense systems are yet to be fully elucidated. This study characterizes the sensitivity of the oocyte to etoposide, a chemotherapeutic agent with the ability to elicit DSBs. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…These results are suggestive that somatic cells are more sensitive to chemotoxicity with the loss of MDRs and/or have more retention of toxins at baseline and even more so with the loss of MDRs compared to oocytes, which were not TUNEL positive nor fluorescently labeled as non-viable with ethidium homodimer-1. Martin et al 2016 reported that incubation with etoposide in vitro is even more toxic to cumulus oophorus complex enclosed oocytes compared to denuded oocytes [55]. This further supports the possibility of increased toxin retention, as we have appreciated anecdotally that comparative efflux assays between oocytes and granulosa cells are technically not feasible because the indicator dye is retained in the granulosa cells to saturating levels.…”
Section: Discussionmentioning
confidence: 81%
“…These results are suggestive that somatic cells are more sensitive to chemotoxicity with the loss of MDRs and/or have more retention of toxins at baseline and even more so with the loss of MDRs compared to oocytes, which were not TUNEL positive nor fluorescently labeled as non-viable with ethidium homodimer-1. Martin et al 2016 reported that incubation with etoposide in vitro is even more toxic to cumulus oophorus complex enclosed oocytes compared to denuded oocytes [55]. This further supports the possibility of increased toxin retention, as we have appreciated anecdotally that comparative efflux assays between oocytes and granulosa cells are technically not feasible because the indicator dye is retained in the granulosa cells to saturating levels.…”
Section: Discussionmentioning
confidence: 81%
“…Immunoprecipitation was conducted as previously described 112 in order to validate proteins targeted for 4-HNE adduction. For each immunoprecipitation assay, 12.5 µg (equivalent to 500 oocytes) were lysed in 200 μl of 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate (CHAPS) lysis buffer comprising 137 mM NaCl, 10% glycerine (v/v), 10 mM CHAPS, 10 mM HEPES and supplemented with ProteCEASE protease inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…We do know that fertilization is followed by a sudden increase in the DNA-repair capacity of the oocyte such that the latter is significantly more resistant to the ability of etoposide to elicit double strand breaks in oocyte DNA. This change is at least partly mediated by the fertilizationdependent upregulation of permeability glycoprotein (PGP), an endogenous multidrug efflux transporter that is translocated to the oolemma and phosphorylated upon oocyte activation, thereby enhancing the ability of the oocyte to remove compounds that might compromise DNA integrity (Martin et al 2016). Many other changes are invoked in the oocyte following fertilization, not least the activation of calcium oscillations by spermspecific phospholipase C. These transients are clearly critical for arresting the tendency of oocytes to descend into an apoptotic decline while activating embryonic development (Swann & Lai 2016).…”
Section: The Oocytementioning
confidence: 99%